An Imitating Wearable Kidney: A Dialectical Replacement For The Cumbersome Dialysis Procedure For Renal Failures - Vishnuvarthanan Govindaraj, Kavipriya Venkatesan,Kiruthish Seethapathy, Sathiyaa Sri Suthanthiram, Saravanan Alagarsamy, Arunprasath Thiyagarajan (International Journal of Advanced Science and Technology, 2020)
The project is determined to endeavor a device, which is a substitute for hemodialysis that benefits the renal failure patient to enrich their life span. Renal failure is the ailment where the functions of natural kidneys fail to meet up their desires like filtration, absorption, secretion and excretion. In general the renal failure patients experience dialysis such as hemodialysis and peritoneal dialysis. Hemodialysis is extensively used because of the downsides in the usage of peritoneal dialysis and hemodialysis procedure is done in hospitals to eradicate wastes from blood to sustain their lives. Hemodialysis makes inopportune to the patient owing to visiting the hospital twice a week and this could be astounded by using wearable dialysis. Wearable dialysis works like hemodialysis that is portable, easy to handle and doesn’t involve any support from the staffs. This contemporary technology which makes possible the progress of wearable dialysis is intended in such a way to give efficacy results.